Assessing the pressure losses during hydrogen transport in the current natural gas infrastructure using numerical modelling - Thawani, Bonny (Cranfield University, 2024)
The UK government aims to transition its modern natural gas infrastructure towards Hydrogen by 2035. Since hydrogen is a much lighter gas than methane, it is important to understand the change in parameters when transporting it. While most modern work in this topic looks at the transport of hydrogen-methane mixtures, this work focuses on pure hydrogen transport. The aim of this paper is to highlight the change in gas distribution parameters when natural gas is replaced by hydrogen in the existing infrastructure. This study uses analytical models and computational models to compare the flow of hydrogen and methane in a pipe based on pressure loss. The Darcy-Weisbach and Colebrook-White equations were used for the analytical models, and the k- ε model was used for the computational approach. The variables considered in the comparison were the pipe material (X52 Steel and MDPE) and pipe diameters (0.01me1m). It was observed that hydrogen had to be transported 250e270% the velocity of methane to replicate flow for a fixed length of pipe. Furthermore, it was noted that MDPE pipes has 2e31% lower pressure losses compared to X52 steel for all diameters when transporting hydrogen at a high velocity.
Keywords: Hydrogen; Natural gas; Modelling and Simulation; Energy; Turbulent Flow; DSDS23; DSDS23 Paper Presentation